2020
DOI: 10.1089/cyber.2019.0273
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Viewing an Uplifting 360-Degree Video on Emotional Well-Being Among Elderly Adults and College Students Under Immersive Virtual Reality and Smartphone Conditions

Abstract: Positive emotions are important for the physical and mental health of elderly adults. Previous research has suggested that the emotion processing mechanisms of elderly adults differ from those of young people. The current study used a mixed-methods approach to explore the emotional impacts of viewing an uplifting 360°v ideos under immersive (using a virtual reality [VR] headset) and nonimmersive (using a smartphone) conditions on elderly populations and young people. In Study 1, we conducted a pre-post treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(85 citation statements)
references
References 19 publications
1
72
0
5
Order By: Relevance
“…A study by Prieto-Pinto et al [ 68 ] found, by using pupillary dilatation measures, which correlates with autonomous nervous system arousal, that men tend to have a greater emotional reaction after being exposed to maternal and neonatal health video clips. In a study conducted in China that aimed to test video versus virtual reality health communications, Liu et al [ 87 ] found that the young and older population differ in positive emotions after being exposed to communication: the young individuals show a greater emotional response to virtual reality, whereas the older individuals show a greater emotional response to health video communication. Of the 39 included studies, trust, which is a key outcome of health communication, was rarely investigated, with only 3 (8%) of the papers included in this review reporting on trust and only 2 (5%) providing empirical evidence regarding the impact of prior mistrust, age, and education on trust.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Prieto-Pinto et al [ 68 ] found, by using pupillary dilatation measures, which correlates with autonomous nervous system arousal, that men tend to have a greater emotional reaction after being exposed to maternal and neonatal health video clips. In a study conducted in China that aimed to test video versus virtual reality health communications, Liu et al [ 87 ] found that the young and older population differ in positive emotions after being exposed to communication: the young individuals show a greater emotional response to virtual reality, whereas the older individuals show a greater emotional response to health video communication. Of the 39 included studies, trust, which is a key outcome of health communication, was rarely investigated, with only 3 (8%) of the papers included in this review reporting on trust and only 2 (5%) providing empirical evidence regarding the impact of prior mistrust, age, and education on trust.…”
Section: Resultsmentioning
confidence: 99%
“…A large amount of research has started to examine the effects of VR in different fields. However, most of these studies have only used student samples, focusing on how young people respond to this new technology and its effects on younger generations (Liu et al, 2020). It is undeniable that young people are a key audience and major users of VR, but since VR has also been widely applied in the medical health area and tourism industry in recent years (Syed-Abdul et al, 2019;Lee and Park, 2020), elderly people could become the main target.…”
Section: Discussionmentioning
confidence: 99%
“…Immersive VR goggles generate more telepresence than a traditional 2D broadcasting device (Shen et al, 2019), and the influence of telepresence in enhancing consumers' beliefs and attitudes toward brands, products and advertisements has been experimentally confirmed (Coyle and Thorson, 2001;Klein, 2003;Hopkins et al, 2004;Fiore et al, 2005). Nevertheless, most of these studies have focused on how people respond to this new technology and its effects on younger generations, but we do not know whether these effects exist in all age groups (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As the theory related to difference equations continues to evolve, scholars have encountered two major difficulties, the first being that the models describing the problem are too complex; as the complexity of the system model increases, one's ability to accurately depict the relevant properties of the model decreases, so that models built for real-world problems have difficulty in perfectly presenting the nature of the problem [1][2][3][4]. e second difficulty relates to the uncertainty caused by the inability to accurately describe the actual situation.…”
Section: Introductionmentioning
confidence: 99%